Decay of mesoscale flux transfer events during quasi‐continuous spatially extended reconnection at the magnetopause. Issue 10 (21st May 2016) - Hasegawa, H.; Kitamura, N.; Saito, Y.; Nagai, T.; Shinohara, I.; Yokota, S.; Pollock, C. J.; Giles, B. L.; Dorelli, J. C.; Gershman, D. J.; Avanov, L. A.; Kreisler, S.; et al.
Abstract: We present observations on 2 October 2015 when the Geotail spacecraft, near the Earth's equatorial plane, and the Magnetospheric Multiscale (MMS) spacecraft, at midsouthern latitudes, simultaneously encountered southward jets from dayside magnetopause reconnection under southward interplanetary magnetic field conditions. The observations show that the equatorial reconnection site under modest solar wind Alfvén Mach number conditions remained active almost continuously for hours and, at the same time, extended over a wide range of local times (≥4 h). The reconnection jets expanded toward the magnetosphere with distance from the reconnection site. Geotail, closer to the reconnection site, occasionally encountered large‐amplitude mesoscale flux transfer events (FTEs) with durations about or less than 1 min. However, MMS subsequently detected no or only smaller‐amplitude corresponding FTE signatures. It is suggested that during quasi‐continuous spatially extended reconnection, mesoscale FTEs decay as the jet spatially evolves over distances between the two spacecraft of ≥350 ion inertial lengths. Key Points: Evidence of quasi‐continuous and spatially extended magnetopause reconnection for southward IMF Broadening toward the magnetosphere of the reconnection jet with distance from the X line Mesoscale flux transfer events decay as the jet evolves with distance from the X line